Growth of 3He crystals at different magnetic fields: Твердый гелий - Bueno, J.; Blaauwgeers, R.; Parshin, A.Y.; Jochemsen, R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
The experiments on 3He crystal growth are carried out in magnetic field up 9 T. The data were analyzedand compared with the results found at zero magnetic field. It was found that the interface and the crystal lattice couple weakly in the presence of an external magnetic field, and we could set an upper limit of the step energy of the <110>, <100> and <211> facets at different magnetic fields.